New Plant Growth-Promoting, Chromium-Detoxifying Microbacterium Species Isolated From a Tannery Wastewater: Performance and Genomic Insights - Ouertani, Rania; Ouertani, Awatef; Mahjoubi, Mouna; Bousselmi, Yosra; Najjari, Afef; Cherif, Hanene; Chamkhi, Asma; Mosbah, Amor; Khdhira, Hechmi; Sghaier, Haitham; Chouchane, Habib; Cherif, Ameur; et al. (Frontiers in Bioengineering and Biotechnology, 2020)
Hexavalent chromium [Cr(VI)], widely generated by tannery activities, is considered among the most toxic substances and causes a serious damage for the environment and for human health. Interestingly, some microorganisms have a potential of bioremediation of chromium-contaminated wastewaters and soils through the reduction of Cr(VI) (Soluble and harmful form) into Cr(III) (Stable and non-toxic form). Here, we present the full genome sequence of a novel heavy-metal-resistant, plant growth-promoting bacterium (PGPB), Microbacterium metallidurans TL13, which was isolated from a Tunisian leather industry. The strain TL13 was resistant to many heavy metals, such as chromium, copper, nickel, cobalt and arsenic. The 50% TL13 growth inhibitory concentration (IC50) values of HgCl2, CoCl2, K2Cr2O7, CuSO4, NiCl2, FeSO4 and Na2HAsO4 are 368, 445, 676, 1590, 1680, 4403 and 7007 mg/L, respectively, with the following toxicity order: HgCl2 > CoCl2 > K2Cr2O7 > CuSO4 > NiCl2 > FeSO4 > Na2HAsO4. This new strain was also able to promote the growth of the hybrid tomato (ELIKA F1) under chromium metal stress. Its whole genome sequence length was estimated to be 3,587,460 bp (3393 coding sequences) with a G+C content of 70.7%. Functional annotation of the genome of TL13 revealed the presence of open reading frames (ORF) involved in adaptation to metal stress, such as the chromate transport protein, cobalt-zinc-cadmium resistance protein, copper resistance protein, copper responsive transcriptional regulator, multidrug resistance transporters, arsenical resistance operon repressor, arsenate reductase, arsenic resistance protein, mercuric resistance operon regulatory protein, mercuric ion reductase and organomercurial lyase. Moreover, genes for the production of glutathione peroxidase, catalase, superoxide dismutase and thioredoxin reductase, which confer a higher tolerance to oxidative/metal stresses, were identified in TL13 genome. In addition, genes for heat shock tolerance, cold shock tolerance, glycine-betaine production, mineral phosphate solubilization, ammonia assimilation, siderophores, exopolysaccharides, polyketides and lytic enzymes (cellulase, chitinase and proteases) production that enable bacteria to survive biotic/abiotic stress and to promote plant growth and health, were also revealed. Based on genome analysis and experimental approaches, strain TL13 appears to have evolved various metabolic strategies and could play a role in ensuring sustainable environmental and agricultural systems.